PRELIMINARY STUDY: COLLABORATION SKILLS IN SCIENCE LESSONS FOR GRADE IV PRIMARY SCHOOL LEARNERS - Urmila Umardianti; Fery Muhammad Firdaus; Kinanti Pangestu (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
Collaboration skills as part of the urgency of learning in the 21st century have a crucial position for elementary school students. The discourse on increasing research in the field of education is not in line with the lack of research that discusses students' collaboration skills to participate in groups comprehensively. This study aims to fill this gap by exploring the initial condition of collaboration skills of 126 grade IV students in three elementary schools in Sleman Regency, Yogyakarta in depth. The researcher detailed the results of the case study analysis on students' collaboration skills in elementary school. One hundred and twenty-six grade IV students in three elementary schools in Sleman district were selected for observation. Semi-structured observations, semi-structured interviews, and several documents are present as instruments to collect data on initial conditions related to students' collaboration skills. The results show the need to develop students' collaboration skills through learning media innovations that are oriented to the characteristics of diverse student learning styles. This study has implications for the importance of improving students' collaboration skills in science learning in the curriculum through learning media innovations that are tailored to the needs of students' learning styles and can provide independent learning guidelines for students in preparing themselves to face the demands of 21st century skills.